Delphi consensus on gene therapy of spinal muscular atrophy with onasemnogene abeparvovec in Germany, Austria and Switzerland – part II – expert based recommendations for surveillance and management of side-effects - Andreas Ziegler; Claudia Weiß; Katharina Vill; Matthias Baumann; Günther Bernert; Astrid Blaschek; Astrid Eisenkölbl; Marina Flotats-Bastardas; Johannes Friese; Dorothea Holzwarth; Claudia Ganter; Klaus Goldhahn; et al. (Journal of Neuromuscular Diseases, 2026)
Background: Systematic protocols for long-term surveillance of children with spinal muscular atrophy treated with onasemnogene abeparvovec are lacking. Together with best practice recommendations for safety monitoring and management, such recommendations should increase patient safety and confidence levels of healthcare providers. Objective: Based on systematic literature review and evidence grading from part 1, this initiative aims to develop a structured treatment plan applicable across all treatment centers in Germany, Austria and Switzerland. Additionally, it seeks to establish consensus recommendations for the clinical management of safety alerts. Methods: Part 2 describes the methodology used to formulate Delphi consensus statements, the development of a structured treatment plan for OA treatment, and the anonymous consensus voting process with standardized follow-up in case of disagreement. Results: A total of 12 consensus statements were developed, addressing diagnostic work-up, safety evaluation, and best practice management of common adverse drug reactions associated with OA gene therapy. All statements achieved >95% consensus in the anonymous Delphi voting. Additionally, two consensus recommendations for handling of positive newborn screening result achieved consensus of 97% and 87%, respectively. A structured treatment plan for gene therapy was consented with 100% agreement, as were standardized recommendations for laboratory testing and a consensus-based algorithm for management of liver transaminase elevations. Conclusions: Delphi-based expert recommendations, developed in co-creation with patient representatives, provide a framework to minimize complications associated with gene therapy and establish the basis for standardized post-marketing data collections. The methodology used in this Delphi-consensus-group can serve as a blueprint for future gene therapy approvals.